Subinhibitory Concentrations of Fusidic Acid May Reduce the Virulence of S. aureus by Down-Regulating sarA and saeRS to Reduce Biofilm Formation and α-Toxin Expression - Liu, Li; Shen, Xiaofei; Yu, Jingyi; Cao, Xingwei; Zhan, Qing; Guo, Yinjuan; Yu, Fangyou (Frontiers in Microbiology, 2020)
Staphylococcus aureus is an important pathogen for hospital and community infections. Fusidic acid is particularly effective in treating skin and wound infections caused by Staphylococci. The purpose of our study was to clarify the effect of fusidic acid on the biofilm formation and α-toxin (encoded by the hla gene) expression of S. aureus at sub-inhibitory concentrations (1/64 × MIC, 1/32 × MIC and 1/16 × MIC). A total of 504 genes greater than a 2- fold or less than -2-fold change in expression of S. aureus effected by sub-inhibitory fusidic acid were found, including 232 up-regulated genes and 272 down-regulated genes, which was determined by transcriptome sequencing. Our results showed sub-inhibitory concentrations of fusidic acid significantly inhibited the expression of hla, spa, icaA and cidA at mRNA level in clinical S. aureus strains tested. And sub-inhibitory concentrations of fusidic acid can significantly reduce the hemolysis activity and α-toxin production of S. aureus. In addition, the sub-inhibitory concentration of fusidic acid significantly inhibited biofilm formation, autolysis, cell aggregation and PIA production of S. aureus. Moreover, fusidic acid reduced the expression of the two-component regulatory system saeRS and staphylococcal accessorygene regulator (sarA). In conclusion, our results suggested that the sub-inhibitory concentrations of fusidic acid may reduce the virulence of S. aureus by down-regulating sarA and saeRS to reduce biofilm formation and α-toxin expression, which will provide a theoretical basis for the clinical treatment of S. aureus infection.